WATASHI GA MITA MIRAI : KAJIAN SEMIOTIKA MODEL CHARLES SANDERS PIERCE - Devina Cahya Putri Sondang; Anak Agung Ayu Dian Andriyani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2023)
This study discusses about dream prediction from the manga Watashi ga Mita Mirai by Tatsuki Ryo. The research type that was used is qualitative research with descriptive method. Data samples were acquired by reading, taking notes, and translating the contents of the manga. The theory was based off Charles Sanders Pierce's Semiothic as the primary source and the manga Watashi ga Mita Mirai by Tatsuki Ryo as the secondary source. Watashi ga Mita Mirai tells the story of dreams predicting things that will happen in the future. One of the dream that will be elevated in this research is the death of Fredie Mercury that has been predicted at 1976.